Generalization of Titchmarsh’s theorem for the Bessel transform in the space L_p,α(ℝ_+) - El Hamma, Mohamed; Daher, Radouan (Annales Mathematicae Silesianae, 2013)
In this paper, we prove a generalization of Titchmarsh’s theorem for the Bessel transform in the space Lp,α(ℝ+) for functions satisfying the (ψ,p)-Bessel Lipschitz condition.